2002
DOI: 10.1046/j.1365-2613.2002.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of alachlor‐induced olfactory mucosal tumours

Abstract: Summary. Alachlor is an herbicide used primarily in the production of corn (maize), peanuts, and soybeans and is associated with cancer of the nasal cavity, thyroid, and stomach in rats. Previous work from our laboratory demonstrated that the nasal cavity tumours originate from the olfactory mucosa, and that neoplasms were present following 6 months of exposure (126 mg/kg/day in the diet). The studies presented herein were conducted to determine more precisely the earliest time point at which alachlor-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
(22 reference statements)
1
15
1
Order By: Relevance
“…The results of the current study, together with previous work in the rat (Genter et al, 2000(Genter et al, , 2002a(Genter et al, , 2002b confirm that there is a marked species difference in response to alachlor between rats and mice. Rats treated chronically with alachlor (126 mg/kg/d) developed treatment-related olfactory tumors with ≥5 months of treatment.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results of the current study, together with previous work in the rat (Genter et al, 2000(Genter et al, , 2002a(Genter et al, , 2002b confirm that there is a marked species difference in response to alachlor between rats and mice. Rats treated chronically with alachlor (126 mg/kg/d) developed treatment-related olfactory tumors with ≥5 months of treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Rats treated chronically with alachlor (126 mg/kg/d) developed treatment-related olfactory tumors with ≥5 months of treatment. The progression of these tumors to more malignant phenotypes was accompanied by cytoplasmic accumulation and nuclear localization of β-catenin, and an observation that is suggestive of activation of Wnt signaling (U.S. EPA, 1985;Genter et al, 2000Genter et al, , 2002aGenter et al, , 2002b. In contrast, in the present study, we found no neoplastic changes in any of the 3 strains examined (treated at a higher dose of 260 mg/kg/d).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The 10 d time point was chosen based on previous data that showed significant dysregulation of olfactory mucosal antioxidant levels with alachlor treatment at very early treatment time points (Burman et al, 2003); further, oxidative stress has been associated with upregulation of matrix metalloproteinases in other model systems (Siwik et al, 2001; Uemura et al, 2001). The 2 mo time point was selected based on prior data from our lab that the earliest histological changes seen in the OM of alachlor-treated rats occurred following 3 mo of treatment (Genter et al, 2002a). Euthanasia was via carbon dioxide asphyxiation, and tissues were snap frozen on dry ice and maintained at –80°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…following 2 mo of chloracetanilide treatment, is prior to the development of any histological changes (Genter et al, 2002a), because we wanted to monitor very early changes in gene expression that might predict a carcinogenic response. Frozen olfactory tissue (50 – 100 mg) was homogenized in Tri Reagent (Molecular Research Center, Cincinnati, OH) and RNA was isolated from the homogenate per the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%